Differentiated Regional Homogeneity in Progressive Mild Cognitive Impairment: A Study With Post Hoc Label. Issue 6 (September 2018) - Cai, Suping; Wang, Yubo; Kang, Yafei; Wang, Haidong; Kim, Hyejin; von Deneen, Karen M.; Huang, Meiping; Jiang, Yuanyuan; Huang, Liyu
Purpose: Mild cognitive impairment (MCI) is considered to be the clinical transition stage between patients with cognitively intact geriatrics and Alzheimer's disease (AD). When observed longitudinally, however, a certain proportion of patients with MCI are expected to revert to a cognitively intact state (MCI_R) while others either remain in the MCI state (MCI_S) or deteriorate into AD (MCI_P). It is worthwhile to investigate the divergence in the brain activities of these MCI groups with different post hoc labels. Methods: In this study, we employed the regional homogeneity (ReHo) measure to explore the characteristics of local brain activity in these MCI groups. Results: Compared to age-matched normal controls, our results exhibited that (1) in MCI_R group, ReHo index showed an increase in the left insula and a decrease in the left superior temporal gyrus; (2) in MCI_S group, ReHo index increased in the left orbital part of the inferior frontal gyrus (IFG_orb) and decreased in the left inferior parietal lobe; and (3) in MCI_P group, ReHo index elevated in the left IFG_orb and decreased in the left putamen. Conclusions: The distinct ReHo changes in the individual MCI groups indicated a potential evidence for differentially active interventions for a specific patient with MCI.